Natural ramie-based composite hydrogel electrolyte and flexible zinc-based battery

CN122968463APending Publication Date: 2026-10-23SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611451025.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]然而,水系锌离子电池的商业化应用仍面临关键瓶颈:传统液态电解质存在漏液、挥发等问题,且易诱发锌枝晶无序生长、析氢、腐蚀及钝化等副反应,导致电池库仑效率快速衰减、循环寿命缩短,甚至引发内部短路

Benefits of technology

本发明通过碱液提取法同步回收苎麻韧皮部的纤维和胶质,将原本作为脱胶废液排放的苎麻胶质转化为高附加值的电池电解质原料,采用高效、环保的草酸二水合物-氯化胆碱酸性DES对苎麻纤维进行羧化改性,将苎麻胶质与羧化纳米纤维混合后进行铸模,构建了具有三维互穿网络结构的复合水凝胶电解质基体;一方面,苎麻胶富含羟基、羧基等极性基团,与高羧基含量纳米纤维形成强氢键作用,不仅提升了复合水凝胶的机械强度和柔韧性,还大幅增加了锌离子络合位点,可有效锚定锌离子、均匀化锌离子通量,降低锌成核过电位,引导均匀沉积,从而抑制锌枝晶、析氢、腐蚀等界面副反应,显著提升了锌负极界面稳定性与水系锌离子电池的电化学性能;另一方面,苎麻为天然生物质资源,本发明将原本作为脱胶废液排放的苎麻胶质转化为高附加值的电池电解质原料,实现了天然苎麻的全组分高值化利用,既解决了传统苎麻脱胶行业的废液污染问题,又大幅降低了水系锌离子电池凝胶电解质的原料成本,符合绿色低碳的发展理念,具备显著的环保与经济效应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968463A_ABST
    Figure CN122968463A_ABST
Patent Text Reader

Abstract

The application discloses a kind of composite hydrogel electrolyte based on natural ramie and flexible zinc-based battery, it is related to battery technical field.Composite hydrogel electrolyte is prepared by the following steps: natural ramie is treated using alkali extraction method, and degummed fiber and ramie gum are simultaneously separated; acid DES is prepared and is used to modify degummed fiber carboxylation, and carboxylated nanofiber dispersion is prepared; carboxylated nanofiber dispersion and ramie gum are compounded according to certain proportion, and appropriate amount of glycerol is added for plasticizing; after casting, drying is carried out to form composite film, and then the composite film is soaked in zinc ion solution for activation; finally, ramie-based composite hydrogel electrolyte is obtained.The composite hydrogel electrolyte based on natural ramie has high ionic conductivity, excellent mechanical properties and interface compatibility, realizes the synergistic improvement of ramie full-component high-value utilization and battery performance, and is low in cost, environmentally friendly in process, and renewable in raw materials, suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a composite hydrogel electrolyte based on natural ramie and a flexible zinc-based battery. Background Technology

[0002] With the rapid development of the renewable energy industry, high-safety, low-cost, long-life, and environmentally friendly electrochemical energy storage technology has become a core requirement in the energy sector. Aqueous zinc-ion batteries, using water as the electrolyte solvent, possess significant advantages such as intrinsic non-flammability and no explosion risk. Furthermore, metallic zinc has high crustal abundance and a high theoretical specific capacity (820 mAh g). -1 With its moderate redox potential (-0.76V vs. SHE), it has shown great application potential in fields such as large-scale energy storage and flexible electronics.

[0003] However, the commercial application of aqueous zinc-ion batteries still faces key bottlenecks: traditional liquid electrolytes suffer from problems such as leakage and volatilization, and are prone to inducing side reactions such as disordered zinc dendrite growth, hydrogen evolution, corrosion, and passivation, leading to rapid decay of battery coulombic efficiency, shortened cycle life, and even internal short circuits. Hydrogel electrolytes can improve these problems, but existing hydrogel electrolytes generally suffer from drawbacks such as difficulty in balancing mechanical properties and ionic conductivity, and poor interface compatibility, making it difficult to effectively control zinc ion deposition behavior and meet the application requirements for long-cycle batteries. Furthermore, most hydrogel electrolytes rely on petroleum-based polymer raw materials, which are environmentally unfriendly and do not align with the trend of green energy storage development. Summary of the Invention

[0004] The present invention aims to prepare a green and environmentally friendly composite hydrogel electrolyte with excellent mechanical and electrochemical properties using natural ramie material, and to prepare an aqueous zinc-ion battery using the composite hydrogel electrolyte.

[0005] The composite hydrogel electrolyte based on natural ramie provided by this invention is prepared through the following steps: S1, the dried ramie bast is soaked in an alkaline aqueous solution for degumming treatment to obtain the separated glue and degummed fibers; S2, the adhesive solution is purified and dried to obtain ramie adhesive; the degummed fibers are dispersed in acidic DES for carboxylation modification to obtain carboxylated fibers, wherein the acidic DES is an acidic deep eutectic solvent formed by oxalic acid dihydrate and choline chloride; the carboxylated fibers are dispersed in deionized water, and the carboxylated fibers are defibrinated and centrifuged to remove coarse fibers to obtain a carboxylated nanofiber dispersion; S3, the ramie gum and carboxylated nanofiber dispersion are mixed in a preset ratio, glycerol is added to the mixed solution and stirred, and then degassed to obtain a casting solution; S4, the casting solution is spread evenly in the mold, dried to remove the solvent and cooled to room temperature to obtain a ramie-based composite film; S5, the ramie-based composite membrane is immersed in a zinc ion solution to obtain a composite hydrogel electrolyte based on natural ramie.

[0006] Optionally, the alkaline aqueous solution is a sodium carbonate aqueous solution, wherein the amount of sodium carbonate in the alkaline aqueous solution is 10% to 25% of the mass of the ramie phloem, and the solid-liquid ratio of the ramie phloem to the alkaline aqueous solution is 1:10 g / mL. -1 The degumming treatment temperature is 100~130℃, and the treatment time is 30~120min.

[0007] Optionally, the purification and drying of the adhesive solution includes the following steps: Dilute hydrochloric acid was added to the adhesive solution to adjust the pH value to neutral. Then, the adhesive solution was washed with deionized water and ethanol to remove impurities. After washing, the adhesive solution was centrifuged and then dried to obtain ramie adhesive.

[0008] Optionally, in the acidic DES, the molar ratio of oxalate dihydrate to choline chloride is 1:1 to 2:1, and the acidic DES is prepared by the following method: Oxalic acid dihydrate and choline chloride were mixed in a certain proportion, and the mixture was stirred at 60~90℃ until a uniform and transparent liquid was formed. After cooling to room temperature, acidic DES was obtained.

[0009] Optionally, in step S2, the solid-liquid ratio of the degummed fiber to acidic DES is 1:20 to 1:100 g / mL. -1 The carboxylation modification reaction temperature is 80~100℃, and the reaction time is 6~12h.

[0010] Optionally, the fiber unwinding process is performed using a high-speed homogenizer, the parameters of which include: The high-speed homogenizer has a rotation speed of 10,000 to 20,000 rpm and a processing time of 30 to 120 min. The centrifugation speed is 4,000 to 8,000 rpm and the centrifugation time is 3 to 8 min. The solid content of the carboxylated nanofiber dispersion is 0.5 to 2 wt%.

[0011] Optionally, in step S3, the mass ratio of the ramie gum to the carboxylated nanofibers in the carboxylated nanofiber dispersion is 4:1 to 1:1, the amount of glycerol added is 5 to 20 wt% of the total mass of the ramie gum and the carboxylated nanofibers, and the total solid content of the casting solution is 1 to 3 wt%.

[0012] Optionally, in step S4, the drying temperature is 50~80℃, the drying time is 12~24h, and the thickness of the ramie-based composite film is 50~200μm.

[0013] Optionally, the zinc ion solution is a zinc sulfate solution, and the concentration of the zinc sulfate solution is 2 mol / L. -1 Soaking time is 12-36 hours.

[0014] The flexible zinc-based battery provided by the present invention includes a negative electrode, a positive electrode, and an electrolyte, wherein the electrolyte is the composite hydrogel electrolyte based on natural ramie as described above.

[0015] The present invention has the following beneficial effects: This invention utilizes an alkaline extraction method to simultaneously recover fibers and gums from the bast layer of ramie, transforming ramie gum, originally discharged as degumming waste, into a high-value-added battery electrolyte raw material. Highly efficient and environmentally friendly oxalate dihydrate-choline chloride acidic DES is used to carboxylate-modify ramie fibers. The ramie gum is then mixed with carboxylated nanofibers and molded to construct a composite hydrogel electrolyte matrix with a three-dimensional interpenetrating network structure. On one hand, ramie gum is rich in polar groups such as hydroxyl and carboxyl groups, forming strong hydrogen bonds with nanofibers high in carboxyl content. This not only enhances the mechanical strength and flexibility of the composite hydrogel but also significantly increases zinc ion complexation sites, effectively anchoring... By fixing and homogenizing zinc ion flux, reducing zinc nucleation overpotential, and guiding uniform deposition, this invention suppresses interfacial side reactions such as zinc dendrite formation, hydrogen evolution, and corrosion, significantly improving the interfacial stability of the zinc anode and the electrochemical performance of aqueous zinc-ion batteries. Furthermore, ramie is a natural biomass resource. This invention transforms ramie gum, originally discharged as degumming wastewater, into a high-value-added battery electrolyte raw material, achieving high-value utilization of all components of natural ramie. This solves the wastewater pollution problem of the traditional ramie degumming industry and significantly reduces the raw material cost of aqueous zinc-ion battery gel electrolytes, aligning with the green and low-carbon development concept and demonstrating significant environmental and economic benefits. Attached Figure Description

[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a flowchart illustrating some embodiments of the preparation method of the composite hydrogel electrolyte based on natural ramie according to the present invention; Figure 2 This is a schematic diagram of the process flow of some embodiments of the preparation method of the composite hydrogel electrolyte based on natural ramie of the present invention; Figure 3The Fourier transform infrared (FT-IR) spectra of ramie gum, carboxylated nanofibers, and ramie-based composite hydrogel in Example 1 of this invention are shown. Figure 4 This is a transmission electron microscope (TEM) image of the carboxylated nanofibers in Example 1 of the present invention. Figure 5 This is a scanning electron microscope (SEM) image of the cross-section of the ramie-based composite hydrogel in Example 1 of the present invention. Figure 6 This is a comparison chart of the room temperature ionic conductivity of the hydrogel electrolytes in Example 1 of the present invention and Comparative Examples 1-3; Figure 7 The zinc symmetric cells of Example 1 and Comparative Examples 1-3 of this invention were tested at 1 mA cm⁻¹. -2 / 1mAh cm -2 Voltage-time cycle curve under the given conditions; Figure 8 The zinc-iodine full cells of Example 1 and Comparative Example 3 of this invention were tested at 1 A g. -1 Cyclic performance at current density; Figure 9 The graphs show the rate performance of zinc-iodine full cells in Example 1 and Comparative Example 3 of this invention. Figure 10 Images of a hygrometer illuminated under different destructive conditions when the battery is assembled according to Embodiment 1 of the present invention. Detailed Implementation

[0018] To make the objectives, features, and advantages of this invention more apparent and understandable, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the embodiments described below are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0019] Experimental methods in the embodiments of this invention that do not specify specific conditions are generally performed under conventional conditions and conditions described in the manual, or under conditions recommended by the manufacturer; the general equipment, materials, reagents, etc. used are commercially available unless otherwise specified.

[0020] Ramie is a natural biomass resource with high cellulose content and excellent mechanical strength. Ramie gum is rich in polar groups such as hydroxyl and carboxyl groups, and has good film-forming properties, adhesion and ion complexing ability. Therefore, ramie is expected to become an ideal raw material for preparing biomass-based energy storage materials. This invention proposes a composite hydrogel electrolyte based on natural ramie.

[0021] See Figure 1, 2 In this embodiment of the invention, the composite hydrogel electrolyte based on natural ramie is prepared through steps S1 to S5: S1, the bast of ramie is soaked in an alkaline aqueous solution and degummed by stirring at a constant temperature. After the reaction is completed, the separated glue and degummed fibers are obtained by filtration.

[0022] In some specific embodiments, the alkaline aqueous solution is a sodium carbonate aqueous solution, and the amount of sodium carbonate in the alkaline aqueous solution is 10% to 25% of the mass of ramie phloem. The solid-liquid ratio of ramie phloem to alkaline aqueous solution is 1:10 g / mL. -1 The degumming treatment temperature is 100~130℃, and the treatment time is 30~120min.

[0023] S2, the adhesive solution is purified and dried to obtain ramie adhesive; the degummed fibers are dispersed in acidic DES for carboxylation modification to obtain carboxylated fibers, where acidic DES is an acidic deep eutectic solvent formed by oxalic acid dihydrate and choline chloride; the carboxylated fibers are dispersed in deionized water, and after defibrination by a high-speed homogenizer and centrifugation to remove coarse fibers, a carboxylated nanofiber dispersion is obtained.

[0024] In some specific embodiments, the purification and drying of the adhesive solution includes the following steps: adding dilute hydrochloric acid to the adhesive solution to adjust the pH value to neutral, then washing the adhesive solution with deionized water and ethanol to remove impurities, and then drying the washed adhesive solution after centrifugation to obtain ramie adhesive.

[0025] In some specific embodiments, the molar ratio of oxalate dihydrate to choline chloride in acidic DES is 1:1 to 2:1. Acidic DES is prepared by the following method: oxalate dihydrate and choline chloride are mixed in a certain ratio, the mixed solution is stirred at 60 to 90°C until a uniform and transparent liquid is formed, and then cooled to room temperature to obtain acidic DES.

[0026] The solid-liquid ratio of degummed fiber to acidic DES is 1:20~1:100 g / mL. -1 The carboxylation modification reaction temperature is 80~100℃ and the reaction time is 6~12h. After the carboxylation modification is completed, the reaction can be terminated by adding excess deionized water to the reaction solution containing carboxylated cellulose. After the reaction is terminated, the supernatant is removed by centrifugation, and the precipitate is repeatedly washed with deionized water until neutral to obtain purified carboxylated cellulose.

[0027] Fiber carboxylation modification is the core means to improve the ability to regulate zinc ions. Existing technologies mostly use the tetramethylpiperidine oxide / sodium bromide / sodium hypochlorite (TEMPO / NaBr / NaClO) oxidation system. However, TEMPO reagent is highly toxic and expensive. The reaction process requires strict pH control, and wastewater treatment is difficult and costly. Traditional inorganic acid carboxylation has problems such as harsh reaction conditions, equipment corrosion, and severe cellulose degradation.

[0028] In this embodiment of the invention, the oxalate dihydrate-choline chloride acidic deep eutectic solvent (DES) is simple to prepare, has low volatility, is biodegradable, can achieve efficient carboxylation modification of cellulose under mild conditions, has controllable carboxyl content, and the solvent is recyclable.

[0029] In some specific embodiments, the parameters for the high-speed homogenizer defiberization process include: a high-speed homogenizer speed of 10,000~20,000 rpm, a processing time of 30~120 min, a centrifugation speed of 4,000~8,000 rpm, a centrifugation time of 3~8 min, and a solid content of 0.5~2 wt% in the carboxylated nanofiber dispersion; after the high-speed homogenizer defiberization process, centrifugation removes the coarse fibers that are not completely defiberized, and the upper uniform dispersion is taken to obtain the carboxylated nanofiber dispersion.

[0030] The conversion of carboxylated fibers into nanofibers is the key to the preparation of high-performance gel electrolytes. Existing methods such as high-pressure homogenization, ball milling, and ultrasonication generally suffer from problems such as high equipment requirements, low processing efficiency, non-uniform nanofiber size, and poor batch stability. High-speed homogenizers are simple to operate, have high fiber dissociation efficiency, controllable nanofiber size, and can be produced continuously. When combined with the above-mentioned DES carboxylation system, green and large-scale preparation of carboxylated nanofibers can be achieved.

[0031] S3, ramie gum and carboxylated nanofiber dispersion are mixed at a preset mass ratio, glycerol is added to the mixed solution and stirred evenly, and then degassed to obtain casting solution.

[0032] This step involves dissolving ramie gum in deionized water to prepare a gum solution, mixing it with a carboxylated nanofiber dispersion at a preset mass ratio, and then adding glycerol as a plasticizer.

[0033] In some specific embodiments, the mass ratio of ramie gum to carboxylated nanofibers in the dispersion is 4:1 to 1:1, the amount of glycerol added is 5 to 20 wt% of the total mass of ramie gum and carboxylated nanofibers, and the total solid content of the casting solution is 1 to 3 wt%.

[0034] S4. The casting solution is spread evenly in the mold, dried to remove the solvent, and cooled to room temperature to obtain a ramie-based composite membrane.

[0035] In some specific embodiments, polytetrafluoroethylene (PTFE) molds are selected.

[0036] In some specific embodiments, the drying temperature is 50~80℃, the drying time is 12~24h, and the thickness of the ramie-based composite film is 50~200μm.

[0037] S5, immerse the ramie-based composite membrane in a zinc ion solution to obtain a composite hydrogel electrolyte based on natural ramie.

[0038] In some specific embodiments, the zinc ion solution is a zinc sulfate solution with a concentration of 2 mol / L. -1 Soaking time is 12-36 hours.

[0039] This invention provides a flexible zinc-based battery, which is an aqueous zinc-ion battery. The flexible zinc-based battery includes a negative electrode, a positive electrode, and an electrolyte. The electrolyte is the composite hydrogel electrolyte based on natural ramie provided in the above embodiment.

[0040] This invention fully leverages the synergistic effect of ramie gum and carboxylated nanofibers to construct a composite hydrogel electrolyte matrix with a three-dimensional interpenetrating network structure. Ramie gum is rich in polar groups such as hydroxyl and carboxyl groups, which form strong hydrogen bonds with nanofibers with high carboxyl content. This not only enhances the mechanical strength and flexibility of the composite hydrogel but also significantly increases the zinc ion complexation sites, effectively anchoring zinc ions, homogenizing zinc ion flux, reducing zinc nucleation overpotential, and guiding uniform deposition. This suppresses interfacial side reactions such as zinc dendrite formation, hydrogen evolution, and corrosion, significantly improving the interfacial stability of the zinc anode and the electrochemical performance of the aqueous zinc-ion battery.

[0041] Furthermore, this invention achieves high-value utilization of all components of natural ramie. By simultaneously recovering degummed ramie fibers and ramie gum through alkaline extraction, the ramie gum, originally discharged as degumming waste liquid, is transformed into a high-value-added battery electrolyte raw material. This solves the waste liquid pollution problem in the ramie degumming industry and significantly reduces the raw material cost of gel electrolytes, aligning with the green and low-carbon development concept and demonstrating significant environmental and economic benefits. The overall preparation process of this invention is simple, with mild reaction conditions and low equipment requirements. It does not use toxic or harmful reagents and can achieve synergistic integration of the ramie degumming, fiber modification, and electrolyte preparation industrial chain. It is suitable for large-scale continuous production and has broad application prospects in the field of energy storage devices such as aqueous zinc-ion batteries and flexible energy storage devices.

[0042] Based on the above embodiments, the present invention also proposes the following specific embodiments. It should be noted that the following specific embodiments are merely exemplary and are not intended to limit the scope of protection of the present invention in any way.

[0043] Example 1: In this embodiment, a composite hydrogel electrolyte based on natural ramie was prepared, and zinc symmetric cells and zinc-iodine full cells were assembled for electrochemical performance testing.

[0044] The preparation steps of the composite hydrogel electrolyte based on natural ramie are as follows: (1) Preparation of ramie glue and degummed ramie fiber: Weigh 14g of ramie and place it in 140mL of 2wt% sodium carbonate aqueous solution. Stir and degumm at 120℃ for 1h. After the reaction, filter and separate to obtain solid degummed ramie fibers and alkaline extract containing gum. Wash the degummed ramie fibers repeatedly with deionized water until neutral and dry them under vacuum at 60℃ for later use. Slowly add 5wt% dilute hydrochloric acid to the alkaline extract to adjust the pH to 7.0. Then add excess ethanol to fully extract the gum. Centrifuge at 8000rpm for 5min, collect the precipitate, wash the precipitate repeatedly with ethanol and deionized water, and dry the washed precipitate at 60℃ for 12h to obtain purified ramie gum.

[0045] (2) Preparation and carboxylation modification of acidic DES: Weigh oxalic acid dihydrate and choline chloride in a molar ratio of 1:1, stir at 80°C for 1 hour until a uniform and transparent liquid is formed, and cool to room temperature to obtain acidic DES; take 1g of degummed ramie fiber, disperse it in 100mL of acidic DES, and stir at 90°C for 12 hours to complete the carboxylation modification.

[0046] (3) Preparation of carboxylated nanofiber dispersion: After the carboxylation modification reaction was completed, 500 mL of deionized water was added to the obtained carboxylated modified fiber to terminate the reaction. The supernatant was removed by centrifugation at 8000 rpm for 5 min. The precipitate was repeatedly washed with deionized water until neutral to obtain purified carboxylated fiber. The carboxylated cellulose was dispersed in deionized water to prepare a suspension with a solid content of 1 wt%. The suspension was processed by a high-speed homogenizer at 12000 rpm for 60 min, and then centrifuged at 6000 rpm for 2 min to remove the coarse fibers in the lower layer that were not completely defibrinated. The upper uniform dispersion was taken to obtain a carboxylated nanofiber dispersion with a solid content of 1 wt%.

[0047] (4) Preparation of casting solution: Weigh 0.3g of purified ramie gum, dissolve it in deionized water to prepare a 2wt% gum solution, mix it with 30g of carboxylated nanofiber dispersion (0.3g) with a solid content of 1wt%, add 0.18g of glycerol (30wt% of the total solid mass), stir at 80℃ for 3h until the mixture is uniform, and degas under vacuum for 30min to obtain a uniform casting solution.

[0048] (5) Preparation of composite membranes: The casting solution was spread evenly in a polytetrafluoroethylene mold and dried at 60°C for 12 hours to obtain a ramie-based composite membrane with a thickness of about 100 μm.

[0049] (6) Preparation of gel electrolyte and battery assembly: The composite membrane was immersed in 2 mol L -1 Ramie-based composite hydrogel electrolyte was obtained by soaking in zinc sulfate aqueous solution for 12 hours.

[0050] A zinc-symmetric cell was assembled using zinc foil as the electrode; a zinc-iodine full cell was assembled using zinc foil as the negative electrode and iodine as the positive electrode, and its electrochemical performance was tested.

[0051] Comparative Example 1: In this comparative example, an unhomogenized composite hydrogel electrolyte based on natural ramie was prepared, and zinc symmetric cells and zinc-iodine full cells were assembled for electrochemical performance testing.

[0052] (1) Preparation of ramie glue and degummed ramie fiber: The steps are the same as steps (1) in Example 1.

[0053] (2) Preparation and carboxylation modification of acidic DES: The steps are the same as step (2) in Example 1.

[0054] (3) Preparation of carboxylated cellulose dispersion: After the carboxylation reaction was completed, 500 mL of deionized water was added to the carboxylated modified fiber to terminate the reaction. The supernatant was removed by centrifugation at 8000 rpm for 5 min. The precipitate was repeatedly washed with deionized water until neutral to obtain purified carboxylated fiber. The carboxylated cellulose was dispersed in deionized water to prepare a suspension with a solid content of 1 wt%. The suspension was treated with magnetic stirring for 60 min without high-speed homogenization. After centrifugation at 6000 rpm for 2 min, the carboxylated fiber dispersion was obtained.

[0055] (4) Preparation of casting solution: Take 0.3g of purified ramie gum, dissolve it in deionized water to prepare a 2wt% gum solution, mix it with 30g of carboxylated cellulose dispersion (0.3g) with a solid content of 1wt%, add 0.18g of glycerol (30wt% of the total solid mass), stir at 80℃ for 3h until the mixture is uniform, and degas under vacuum for 30min to obtain a uniform casting solution.

[0056] (5) Preparation of composite membranes: The same steps as step (5) in Example 1 were followed to obtain an unhomogenized composite membrane with a thickness of approximately 100 μm.

[0057] (6) Preparation of gel electrolyte and battery assembly: The steps are the same as step (6) in Example 1, to obtain an unhomogenized gel electrolyte, and to assemble the corresponding battery for testing.

[0058] Comparative Example 2: In this comparative example, a composite hydrogel electrolyte based on natural ramie with uncarboxylated fiber was prepared, and zinc symmetric cells and zinc-iodine full cells were assembled for electrochemical performance testing.

[0059] (1) Preparation of ramie glue and degummed ramie fiber: The steps are the same as steps (1) in Example 1.

[0060] (2) The degummed fibers were not carboxylated and were directly processed using a high-speed homogenizer: Take 1g of degummed ramie fiber, disperse it in 100mL of deionized water, and process it with a high-speed homogenizer at 12000rpm for 60min. After centrifugation at 6000rpm for 2min, an uncarboxylated nanofiber dispersion with a solid content of 1wt% is obtained.

[0061] (3) Preparation of casting solution: Take 0.3g of purified ramie gum, dissolve it in deionized water to prepare a 2wt% gel solution, mix it with 30g of nanofiber dispersion (0.3g) with 1wt% solid content, add 0.18g of glycerol (30wt% of total solid mass), stir at 80℃ for 3h until uniformly mixed, and degas under vacuum for 30min to obtain a uniform casting solution.

[0062] (4) Preparation of composite membrane: The steps are the same as step (5) in Example 1, and an uncarboxylated composite membrane with a thickness of about 100 μm is obtained.

[0063] (5) Preparation of gel electrolyte and battery assembly: The steps are the same as step (6) in Example 1, to obtain an uncarboxylated modified gel electrolyte, and to assemble the corresponding battery for testing.

[0064] Comparative Example 3: This comparative example uses a commercially available glass fiber diaphragm with a concentration of 2 mol / L. -1 Zinc sulfate aqueous solution was used as the liquid electrolyte. Zinc symmetric cells and zinc-iodine full cells were assembled under the same conditions as in Example 1 and compared.

[0065] The performance test results and analysis are as follows: Figure 5-8In this context, "ramie-based composite hydrogel" refers to the hydrogel electrolyte prepared in Example 1 or the half-cell / battery assembled with the hydrogel electrolyte; "heterogeneous composite hydrogel" refers to the hydrogel electrolyte prepared in Comparative Example 1 or the half-cell / battery assembled with the hydrogel electrolyte; "uncarboxylated composite hydrogel" refers to the hydrogel electrolyte prepared in Comparative Example 2 or the half-cell / battery assembled with the hydrogel electrolyte; and "zinc sulfate" refers to the commercially available membrane system electrolyte used in Comparative Example 3 or the half-cell / battery assembled with the electrolyte.

[0066] Figure 3 The Fourier transform infrared (FT-IR) spectra of ramie gum, carboxylated nanofibers, and ramie-based composite hydrogel in Example 1 are shown. It can be seen that ramie gum exhibits high activity at 3200 cm⁻¹. -1 The characteristic stretching vibration peak of the hydroxyl group appears nearby, at 1640 cm⁻¹. -1 Characteristic absorption peaks of carboxyl groups appeared nearby; carboxylated nanofibers modified with oxalate dihydrate-choline chloride DES showed a peak at 1585 cm⁻¹. -1 The intensity of the characteristic peak of the carboxyl group at the modified cellulose was significantly increased, proving that the modification process achieved efficient carboxylation of cellulose. The composite hydrogel retained the characteristic absorption peaks of both ramie gum and carboxylated nanofibers, and the hydroxyl peak shifted significantly, proving that a strong hydrogen bond interaction was formed between the two, achieving a good composite.

[0067] Figure 4 The image shown is a transmission electron microscope (TEM) image of the carboxylated nanofibers in Example 1. It can be seen that the carboxylated nanofibers prepared by the present invention through high-speed homogenization and centrifugation have a uniform diameter distribution between 10 and 30 nm, a length of 1 to 5 μm, no obvious agglomeration, and a uniform aspect ratio.

[0068] Figure 5 The image shown is a scanning electron microscope (SEM) image of the cross-section of the ramie-based composite hydrogel in Example 1. It can be seen that the composite hydrogel prepared by the present invention has a three-dimensional interconnected porous network structure (top image). After being soaked in zinc sulfate solution (bottom image), the gel electrolyte still maintains the complete porous network structure without obvious collapse, providing a stable channel for the rapid transport and uniform distribution of zinc ions.

[0069] Figure 6 The graph shows a comparison of the room-temperature ionic conductivity of the hydrogel electrolytes in Example 1 and Comparative Examples 1-3. It can be seen that the room-temperature ionic conductivity of the composite hydrogel electrolyte in Example 1 reaches 14.76 mS / cm. -1 This is significantly higher than that of the heterogeneous system in Comparative Example 1 (4.73 mS cm⁻¹). -1 ), and the uncarboxylated system of Comparative Example 2 (5.50 mS cm⁻¹) -1This study demonstrates that high carboxyl content and a uniform nanofiber network can significantly improve the liquid retention capacity and zinc ion migration efficiency of gel electrolytes.

[0070] Figure 7 The zinc symmetric cells of Example 1 and Comparative Examples 1-3 were compared at 1 mA cm⁻¹. -2 / 1mAh cm -2 The voltage-time cycling curves under the given conditions show that the zinc symmetric battery based on the composite hydrogel electrolyte of Example 1 achieves a voltage-time cycling performance of 1 mA cm⁻¹. -2 / 1mAhcm -2 Under the test conditions, it can be stably cycled for over 1100 hours with the polarization voltage consistently below 12mV. In contrast, the heterogeneous system of Comparative Example 1 exhibited severe voltage fluctuations after only 480 hours of cycling, the uncarboxylated system of Comparative Example 2 showed a significant increase in polarization voltage after 870 hours of cycling, and the commercial glass fiber system of Comparative Example 3 experienced a short circuit after 340 hours of cycling. These results fully demonstrate that the gel electrolyte prepared in this invention can effectively guide the uniform deposition of zinc ions, significantly inhibit zinc dendrite growth and interfacial side reactions, thereby improving the interfacial stability and cycle life of the zinc anode.

[0071] Figure 8 The zinc-iodine full cells of Example 1 and Comparative Example 3 were tested at 1 A g. -1 The cycling performance graph at current density shows that the zinc-iodine full cell based on the composite hydrogel electrolyte of Example 1 achieves good cycling performance at 1 A g. -1 At a current density of [value missing], the initial discharge specific capacity reached 132.23 mAh g. -1 After 2000 cycles, the capacity retention rate is still as high as 96.91%, and the coulombic efficiency remains above 99.6%. In contrast, the full cell based on the commercial system of Comparative Example 3 has a capacity retention rate of 78.3% after 2000 cycles, and the coulombic efficiency fluctuates significantly. This fully demonstrates that the hydrogel electrolyte of the present invention can significantly improve the cycle stability of the full cell.

[0072] Figure 9 The graphs show the rate performance of the zinc-iodine full cells in Example 1 and Comparative Example 3. It can be seen that the zinc-iodine full cell based on the composite hydrogel electrolyte of Example 1 achieves a rate performance of 0.2 A g / L at 0.2 A g / L. -1 0.5A g -1 1A g -1 2A g -1 5A g -1 At current densities of 174.45 mAh g, respectively. -1 149.52mAh g -1 135.66mAh g -1 127.00mAh g -1 114.18mAh g-1 The discharge specific capacity, when the current density recovers to 0.2 A g -1 At that time, the specific capacity can be restored to 150.20 mAh g. -1 The system exhibits excellent rate performance and structural reversibility. In contrast, the overall capacity of the commercial membrane system in Comparative Example 3 is lower, which is due to the effects of zinc anode dendrite growth and hydrogen evolution corrosion in the liquid electrolyte. When the current recovers, the recovery is also very small, only 0.2 A g. -1 The specific capacity is only 95.38mAh g. -1 The system could not return to its initial level, indicating that the commercial system in Comparative Example 3 suffered stronger side effects under high current cycling.

[0073] Furthermore, the composite hydrogel electrolyte prepared by this invention exhibits excellent safety. Figure 10 The images of the hygrometer illuminated by the assembled battery in Example 1 under different destructive conditions demonstrate that the zinc-iodine soft-pack full battery based on the composite hydrogel electrolyte in Example 1 can still drive the hygrometer to operate stably after being subjected to mechanical damage such as hammering, puncture, and cutting. In contrast, the commercial diaphragm system in Comparative Example 3 will face a series of problems such as electrolyte leakage and battery short circuit. At the same time, this invention realizes the full utilization of ramie raw materials, the modification process is green and environmentally friendly, and the preparation of nanofibers is simple and efficient. It can be linked with the existing ramie degumming industry chain and has the potential for large-scale industrialization. It has broad application prospects in the field of new energy storage devices such as flexible zinc-based batteries.

[0074] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite hydrogel electrolyte based on natural ramie, characterized in that, Prepared by the following steps: S1, the dried ramie bast is soaked in an alkaline aqueous solution for degumming treatment to obtain the separated glue and degummed fibers; S2, the adhesive solution is purified and dried to obtain ramie adhesive; the degummed fibers are dispersed in acidic DES for carboxylation modification to obtain carboxylated fibers, wherein the acidic DES is an acidic deep eutectic solvent formed by oxalate dihydrate and choline chloride. The carboxylated fibers were dispersed in deionized water, and the carboxylated fibers were defibrilated and centrifuged to remove coarse fibers to obtain a carboxylated nanofiber dispersion. S3, the ramie gum and carboxylated nanofiber dispersion are mixed in a preset ratio, glycerol is added to the mixed solution and stirred, and then degassed to obtain a casting solution; S4, the casting solution is spread evenly in the mold, dried to remove the solvent and cooled to room temperature to obtain a ramie-based composite film; S5, the ramie-based composite membrane is immersed in a zinc ion solution to obtain a composite hydrogel electrolyte based on natural ramie.

2. The composite hydrogel electrolyte based on natural ramie according to claim 1, characterized in that, The alkaline aqueous solution is a sodium carbonate aqueous solution, and the amount of sodium carbonate in the alkaline aqueous solution is 10% to 25% of the mass of the ramie phloem. The solid-liquid ratio of the ramie phloem to the alkaline aqueous solution is 1:10 g / mL. -1 The degumming treatment temperature is 100~130℃, and the treatment time is 30~120min.

3. The composite hydrogel electrolyte based on natural ramie according to claim 1, characterized in that, The purification and drying of the adhesive solution includes the following steps: Dilute hydrochloric acid was added to the adhesive solution to adjust the pH value to neutral. Then, the adhesive solution was washed with deionized water and ethanol to remove impurities. After washing, the adhesive solution was centrifuged and then dried to obtain ramie adhesive.

4. The composite hydrogel electrolyte based on natural ramie according to claim 1, characterized in that, In the acidic DES, the molar ratio of oxalate dihydrate to choline chloride is 1:1 to 2:1, and the acidic DES is prepared by the following method: Oxalic acid dihydrate and choline chloride were mixed in a certain proportion, and the mixture was stirred at 60~90℃ until a uniform and transparent liquid was formed. After cooling to room temperature, acidic DES was obtained.

5. The composite hydrogel electrolyte based on natural ramie according to claim 1, characterized in that, In step S2, the solid-liquid ratio of the degummed fiber to acidic DES is 1:20 to 1:100 g / mL. -1 The carboxylation modification reaction temperature is 80~100℃, and the reaction time is 6~12h.

6. The composite hydrogel electrolyte based on natural ramie according to claim 1, characterized in that, The fiber debonding process uses a high-speed homogenizer. The parameters of the high-speed homogenizer include: The rotation speed is 10,000~20,000 rpm, the processing time is 30~120 min, the centrifugation speed is 4,000~8,000 rpm, and the centrifugation time is 3~8 min; The solid content of the carboxylated nanofiber dispersion is 0.5~2wt%.

7. The composite hydrogel electrolyte based on natural ramie according to claim 1, characterized in that, In step S3, the mass ratio of the ramie gum to the carboxylated nanofibers in the carboxylated nanofiber dispersion is 4:1 to 1:1, the amount of glycerol added is 5 to 20 wt% of the total mass of the ramie gum and the carboxylated nanofibers, and the total solid content of the casting solution is 1 to 3 wt%.

8. The composite hydrogel electrolyte based on natural ramie according to claim 1, characterized in that, In step S4, the drying temperature is 50~80℃, the drying time is 12~24h, and the thickness of the ramie-based composite film is 50~200μm.

9. The composite hydrogel electrolyte based on natural ramie according to claim 1, characterized in that, The zinc ion solution is a zinc sulfate solution with a concentration of 2 mol / L. -1 Soaking time is 12-36 hours.

10. A flexible zinc-based battery, comprising a negative electrode, a positive electrode, and an electrolyte, characterized in that, The electrolyte is the composite hydrogel electrolyte based on natural ramie as described in any one of claims 1-9.